Pertumbuhan Tanaman Selada (Lactuca sativa L. var. New Grand Rapids) menggunakan Teknologi Hidroponik Sistem Terapung (THST) Tanpa Sirkulasi dengan Penambahan Giberelin (GA3) - Riza Linda, Widya Sri Rahayu Mukarlina (Universitas Tanjungpura, 2018)
Lettuce (Lactuca sativa L. var. New Grand Rapids) is a vegetable plant that has a contains high nutrients. Efforts that can increase the production of lettuce is using hydroponics technology and the addition of growth regulators is gibberellin (GA3). This research aims to determine the effect of addition of GA3 to gowth of lettuce using floating technology system of hydroponics without circulation. The research was conducted for four months from May to August 2017 in the Green House and Laboratory of Biology of the Faculty of Mathematics and Natural Sciences, Tanjungpura University Pontianak. This research used a completely randomized design with five treatments (K) and three repetitions. The treatments given is the addition of GA3 with different consentrations: K0 (Control), K1 (5 ppm), K2 (10 ppm), K3 (15 ppm), and K4 (20 ppm). The result showed that the addition of GA3 didn’t significant affect on the number of leaves, but showed a significantly affected the height, root lenght, leaf areas, and fresh weight.